2012
DOI: 10.1177/0194599812459325
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Chemoradiation in Patients with Head and Neck Cancer

Abstract: Despite major improvement in locoregional control rates, CCRT has a significant negative impact on the functional outcomes of head and neck cancer patients, with a high number of patients remaining PEG and tracheotomy dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…The affected domains were ''speech'' and emotional domains, but the change of these domains during recovery were not assessed. Another study evaluated the dependence on tracheotomy tube and showed that the average time of dependence was 11 months [25]. They did not measure QoL but speculated that tracheotomy tube may influence it.…”
Section: Discussionmentioning
confidence: 99%
“…The affected domains were ''speech'' and emotional domains, but the change of these domains during recovery were not assessed. Another study evaluated the dependence on tracheotomy tube and showed that the average time of dependence was 11 months [25]. They did not measure QoL but speculated that tracheotomy tube may influence it.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature continues to show that XRT/CRT have a negative impact on QOL and swallowing function 52 with xerostomia-related complications being the most prominent obstacles for patients to overcome. 53 Minimizing and focusing XRT, while avoiding chemotherapy lead to less treatment toxicity and improved outcomes. 5355 Patients with early stage disease treated with surgery alone, demonstrate superior outcomes by avoiding the toxicity of XRT.…”
Section: Commentmentioning
confidence: 99%
“…53 Minimizing and focusing XRT, while avoiding chemotherapy lead to less treatment toxicity and improved outcomes. 5355 Patients with early stage disease treated with surgery alone, demonstrate superior outcomes by avoiding the toxicity of XRT. 27,54,56 Although this data is still in its infancy, TORS is showing promise as an optimal treatment strategy in early stage disease.…”
Section: Commentmentioning
confidence: 99%
“…The risks for tracheostomy dependence may have multifactorial etiology, including poor laryngeal function prior to treatment as well as radiation toxicity after treatment, leading to laryngeal edema and laryngeal inflexibility as well as chondronecrosis . Some have attempted to identify factors that predict poor laryngeal function, as measured by long‐term tracheostomy . By identifying factors that predict poor functional outcomes after organ preservation therapy, we may better select for patients who would derive the most benefit from toxic chemoradiation regimens.…”
Section: Introductionmentioning
confidence: 99%